2015
DOI: 10.1159/000381655
|View full text |Cite
|
Sign up to set email alerts
|

Civic Purpose: An Integrated Construct for Understanding Civic Development in Adolescence

Abstract: This article introduces civic purpose as a construct for learning about civic development in adolescence. Civic purpose, defined as a sustained intention to contribute to the world beyond the self through civic or political action, integrates the components of motivation, civic activity, and future-oriented civic intention. We present results from a mixed methods longitudinal study that used the civic purpose framework in which 1,578 high school seniors took a survey, 50 participated in an interview, and 9 add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 60 publications
7
126
0
9
Order By: Relevance
“…However, it is intriguing that 25% of politically active youth in this study were motivated by helping identity. Although research has suggested that youth don't see political activities as a way to help others (Walker, 2002), perhaps helping identity is a primary motive for a subset of politically active youth (Malin et al, 2015). It is important to note that because political was not defined in this study, it might be that participants interpreted "political" activities more broadly than in previous research.…”
Section: Motivations For Political and Nonpolitical Volunteering Actimentioning
confidence: 76%
See 2 more Smart Citations
“…However, it is intriguing that 25% of politically active youth in this study were motivated by helping identity. Although research has suggested that youth don't see political activities as a way to help others (Walker, 2002), perhaps helping identity is a primary motive for a subset of politically active youth (Malin et al, 2015). It is important to note that because political was not defined in this study, it might be that participants interpreted "political" activities more broadly than in previous research.…”
Section: Motivations For Political and Nonpolitical Volunteering Actimentioning
confidence: 76%
“…Further research can elaborate on the issues that lead to sustained civic participation and examine how concerns for specific issues integrate with other motivations in highly involved youth. Indeed, a recent analysis of civically purposeful youth from the same study found that youth integrate their interest in social issues with their own social values and identities (Malin, Ballard, & Damon, 2015).…”
Section: Motivations For Political and Nonpolitical Volunteering Actimentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to nonfamilial adults might provide professional models and opportunities for youth (Jarrett, Sullivan, & Watkins, ; Zeldin, Larson, Camino, & O'Connor, ). Second, all three forms of civic activities might serve a social function by putting young people in contact with adult mentors and like‐minded peers who can provide psychological support and shape expectations, aspirations, and goals (Diemer, ; Malin, Ballard, & Damon, ; Zeldin et al., ). Third, meaningful engagement in civic life might engage young people in their education.…”
Section: Civic Engagement and Healthmentioning
confidence: 99%
“…Third, meaningful engagement in civic life might engage young people in their education. At a time when some young people are at risk for disengaging from school, civic opportunities can provide a context for them to derive purpose and find meaning in their lives (Malin et al., ), increase their future orientation and a tendency to plan for the future (Robbins & Bryan, ), and redirect effort toward attaining goals, all of which might lead to more academic engagement and better academic performance. However, it could also be the case that certain forms of civic engagement might funnel people toward career paths in helping or advocacy professions, which may result in lower SES in adulthood.…”
Section: Civic Engagement and Healthmentioning
confidence: 99%